An Analysis of Disciplinary Power Through the Character of Paul Atreides in Dune (2021) - Septa Ayu Andini; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This research analyzes how disciplinary power is represented through the character of Paul Atreides in the film Dune (2021) by drawing on Michel Foucault's theory of disciplinary power. As a political science fiction film, Dune (2021) depicts Paul's journey as the heir to House Atreides, who has been under strict supervision, training, and rules since his birth. This research uses a descriptive qualitative method to analyze scenes, dialogue, and visuals that demonstrate disciplinary practices such as surveillance, normalizing judgment, examinations, training of the body, habit formation, and internalization. The results show that power in Dune (2021) does not operate oppressively, but rather subtly through disciplinary mechanisms that shape Paul's behavior, identity, and self-awareness. This process transforms Paul from a young man under surveillance into someone who manages himself and is ready to become a leader. Overall, this research concludes that power in Dune (2021) plays a significant role in shaping Paul Atreides' identity through six mechanisms of disciplinary power.